A comparative analysis of benthic nematode assemblages from Zostera noltii beds before and after a major vegetation collapse - Materatski, Patrick (2016)
Benthic nematodes are widely regarded as very suitable organisms to monitor potential ecological effects of natural and anthropogenic disturbances in aquatic ecosystems. During 2008, the seagrass beds of Zostera noltii located in the Mira estuary (SW Portugal) disappeared completely. However, during 2009, slight symptoms of natural recovery were observed, a process which has since evolved intermittently. This study aims to investigate changes in patterns of nematode density, diversity, and trophic composition between two distinct habitat conditions: “before” the collapse of seagrass beds, and during the early recovery “after” the seagrass habitat loss, through the analysis of: i) temporal and spatial distribution patterns of nematode communities, and ii) the most important environmental variables influencing the nematode assemblages. The following hypotheses were tested: i) there would be differences in nematode assemblage density, biodiversity and trophic composition during both ecological conditions, “before” and “after”; and ii) there would be differences in nematode assemblage density, biodiversity and trophic composition at different sampling occasions during both ecological conditions. Nematode density and diversity were significantly different between the two ecological situations. A higher density was recorded before, but a higher diversity was evident after the collapse of Z. noltii. In spite of the disturbance caused by the seagrass habitat loss in the Mira estuary, the nematode trophic composition did not significantly differ between the before and after seagrass collapse situations. Despite the significant differences found among sampling occasions, a consistent temporal pattern was not evident. The response of nematode communities following this extreme event exhibited considerable resistance and resilience to the new environmental conditions.